Meningkatkan Kemampuan Mengenal Angka 1-10 pada Anak Usia 4-5 Tahun Melalui Kegiatan Bermain Variatif dengan Media Loose Part - Jarwani Jarwani (AUDIENSI: Jurnal Pendidikan dan Perkembangan Anak, 2022)
This study aims to improve the ability of children to recognize numbers 1-10 in group A TK Sinar Kasih Sangup, Kecamatan Tamansari, Kabupaten Boyolali. This research uses Classroom Action Research (CAR). The research subjects in group A of Sinar Kasih Sangup Kindergarten were 10 children consisting of 6 girls and 4 boys. Data collection techniques in this study are observation and documentation. The data analysis technique used descriptive analysis. The results of this study indicate an increase in children's ability to recognize numbers 1-10 through varied play activities with loose part media, namely in the pre-cycle the ability of children to recognize numbers 1-10 is only 20%, at the first cycle meeting children's ability to recognize numbers 1-10 increases to 40%, in cycle 2 the child's ability to recognize numbers 1-10 increased to 60%, and in cycle 3 the child's ability to recognize numbers 1-10 increased to 80%. The indicator used in this study is that children are able to recognize numbers 1-10. The conclusion of this study is that children are able to recognize numbers 1-10 with varied play activities with loose part media.